Computational teaching in basic education from a comprehensive vision: an ally in Literacy for the Digital Age (APED) - Noriega-Carrasco , María-Guadalupe (2024)
This scientific essay contributes to the theoretical systematization of the elements related to technological and digital literacy in teachers and students, based on the concern that frames the digital and technological competencies currently in demand. Therefore, the objective of this proposal is to carry out a documentary review to understand the educational demands for the digital era, the importance of instrumentalism in technological and digital literacy of the 21st century and the prevailing situation in Mexico, without ignoring some Latin American theoretical visions. The need for training in issues of culture and digital literacy encompasses the entire society, however, the approach revolves around educational settings from two theoretical perspectives: (1) the role of the actors involved, who in addition to the students, the condition of teachers is considered essential; and (2) the teaching and learning processes as a systematized means to influence training processes. The proposal analyzes the difficulties faced in the intention to generate instrumental teaching programs to strengthen the levels of digital literacy (DA) and technological literacy (AT), which are affected for various reasons, such as: age of the participants, educational level where the program is intended to be implemented, absence of assessment in learning because it is not considered a priority and distance in inclusion in the study plans.